PORTRAIT OF THE SOCIO-ECONOMIC LIFE OF FISHERMEN IN PANTAI LABU SUB-DISTRICT, NORTH SUMATRA - Atha Rifqi Wahyudi Silitonga; Muhammad Farhan Pulungan; Muhammad Ihsan Al Kahfi; Habib Aulia; Rasia Azima Putra Haganta Purba (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This research discusses the socio-economy of fishing communities in Pantai Labu District, North Sumatra. The problems studied in the research focused on how to find out the socio-economic life of the delayan community in Pantai Labu District both from the social, social organization, economic organization, social and economic aspects. In the review methodology, they provide a detailed description of the quality, with applied technical data, technical observations and different structures. The results of this study show the socio-economic life of the community ranging from work, income, livelihoods and community environment.